Implementasi Pembiayaan Ultra Mikro Dalam Pengembangan Usaha Mikro Kecil Menengah Dikecamatan Dawe Kudus (Studi Kasus Pada Kspps Artha Bahana Syariah Cabang Dawe Kudus) - Hana Zarima; Wafa Ariska Rahmadiani (Journal of Islamic Banking, 2023)
The purpose of this is to analyze ultra micro financing in MSME in the Dawe sub-district. This research is a qualitative research by conducting direct interviews with the object of research, namely the manager of KSPPS Artha Bahana Syariah Dawe Kudus branch and members of ultramicro financing. Data collection techniques in the form of interviews, observation and documentation of the data analysis technique used is the observation method. The results of this study are the condition of ultra-micro financing which is in great demand by the Dawe community and it can be said that the distribution of ultra-micro financing is good and appropriate. Ultra-micro financing really supports the economy around the area and really helps MSME actors there. Where the distribution of ultra-micro financing funds is evenly distributed around the KSPPS Artha Bahana Dawe branch area.